(untitled) (Journal of Science, Technology and Innovation Policy, 2023)
The constitution of Pakistan, an Islamic democracy, upholds the legal rights of its citizens. However, globalization and liberalization have led the nation to recognize the presence of the third gender, also known as transgender. According to the Transgender (Protection of Rights) Act 2018, Pakistani people are permitted to change their gender from male to female, female to male, or male/female to transgender. The person’s perspective of themselves may play a role in the choice to change gender. By all rights, Pakistan is not the first country to use self-perception as a method for decision-making in order to effect gender change. Therefore, this study is conducted to investigate which other nations are using self-perception as a method for gender change. The study is conducted using quantitative content analysis. The contents of transgender-related acts enacted by numerous nations, including Pakistan will be analyzed using manifest analysis. It is anticipated that the study will provide some insight into how self-perception for gender change is being implemented in Pakistan. Recommendations for future studies are also suggested.